Development of a diagnostic tool for the detection of antibodies against human enterovirus 71 - Tan, Cheng Siang. (Universiti Malaysia Sarawak (UNIMAS), 2004)
The VPI gene from three different genogroup of Human enterovirus 71, namely B3, B4 and C1 were cloned and expressed as C-terminal fusion proteins in E. coli. The VPI gene of HEV71 genogroup B3 was further engineered to express truncated products.